Androgen versus erythropoietin for the treatment of anaemia of pre-dialysis chronic kidney disease - Paul, AK; Latif, ZA; Iqbal, S; Amin, F; Shefin, SM; Ashrafuzzaman, SM (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):125-128 The abstract of this article is available on the PubMed website